Monetary Policy Evaluation using a Rational Expectations Model: the UK case - Aleksandar Vasilev (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This study follows Rotemberg and Woodford (1998) and estimates a three-equation model of output, interest rate and inflation, in order to evaluate alternative rules by which the UK monetary authority may decide on setting the main interest rate. As in the original paper, the model setup is a rational-expectations setup, augmented with nominal price-setting frictions a la Calvo (1983). The model-generated impulse responses match quite well the estimated responses to a monetary shock. In addition, when additional technology and taste shocks are added, the theoretical model can account for the fluctuations in the UK data as well as an unrestricted VAR(1) does.
Keywords: E37; 330; VAR; Taylor rule